Hubungan Strategi Marketing Public Relations dalam Membangun Brand Image PT. GK Invest - Rianti Haifa Khoirunissa; Riza Hernawati (UNISBA Press, 2023)
Abstract. Marketing Public Relations is one of the important things in a company, especially in the Business World. The concept of a marketing public relations strategy can help the development of companies that can improve the brand image of a company, maintaining relationships with the community can further help companies to move better. With a case related to fraudulent investment in the luring of getting short-term profits and being given directions to make accurate investments in the timing of attracting transactions, I took research on